Assessment of Salivary Human Herpesvirus-6 and Immunoglobulin A Levels in Nurses Working Shifts - Hirom Fukuda, RN, PhD; Takamichi Ichinose, PhD; Tomoko Kusama, RN, PHN, PhD; Reico Sakurai, RN, PHN, MS (Elsevier, 2008)
The purpose of the present study was to assess whether salivary human herpesvirus (HHV)-6 acted as a new sensitive stress marker, providing a reliable indicator of stress among shift work nurses. Salivary HHV-6, immunoglobulin (Ig) A and mood states were compared among nurses who worked day shifts only and nurses who worked different numbers of night shifts. Methods: Participants included 56 female nurses working in Japanese general hospitals. The 56 subjects were categorized into three groups: Group A (n = 7), which consisted of nurses who only worked day shifts; group B (n = 29), which consisted of nurses working shifts with £8 night shifts per month; and group C (n = 20), which consisted of nurses working shifts with 3 9 night shifts per month. Mood was assessed using the Profile of Mood States Short Form Japanese version (POMS-SFJ). Salivary biomarker levels and mood were compared among the three groups. Results: Although the salivary HHV-6 level was significantly higher in group C than in group A (p < .05), salivary IgA and mood levels were not significantly different among the three groups. Conclusion: Salivary HHV-6 level may be a more sensitive stress marker than salivary IgA or mood for assessing chronic fatigue in nurses working shifts. Improvement to shift assignments using assessment by salivary HHV-6 is required.